REPRESENTASI SITUASI SOSIAL DAN KONSTRUKSI IDEOLOGI DALAM PIDATO PELANTIKAN ANIES BASWEDAN - Rinta Alvionita (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract. Representation of Social Situation and Ideology Construction in Anies Baswedan’s Inauguration Speech. This research investigates the representataion of the social situations of Jakarta current issues found in Anies Baswedan’s speech at Governor and Vice Governor inauguration and the reveal of ideology as reflected in the speech. The method used in this research is a qualitative-critical linguistic focusing on the analysis of language metafunctions. The results indicate that the representation of the social situation in DKI Jakarta in view of Anies Baswedan's speech reflects certain ideology depicting the criticism and the spotlight on the issue of justice, prosperity, colonialism, indigenous and independence. This ideology is somewhat based on the use of language in his speech as an attempt to shape the self-image of having efforts to be 'a pro-people and better governor'.